2015
DOI: 10.2147/copd.s94377
|View full text |Cite|
|
Sign up to set email alerts
|

The Short Physical Performance Battery is a discriminative tool for identifying patients with COPD at risk of disability

Abstract: BackgroundLimited mobility is a risk factor for developing chronic obstructive pulmonary disease (COPD)-related disabilities. Little is known about the validity of the Short Physical Performance Battery (SPPB) for identifying mobility limitations in patients with COPD.ObjectiveTo determine the clinical validity of the SPPB summary score and its three components (standing balance, 4-meter gait speed, and five-repetition sit-to-stand) for identifying mobility limitations in patients with COPD.MethodsThis cross-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
75
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(75 citation statements)
references
References 28 publications
(44 reference statements)
0
75
0
Order By: Relevance
“…Since its development, numerous studies have shown discrimination ability of the SPPB in evaluating the functional status of older adults. For instance, studies have shown that worse physical performance based on the SPPB is associated in older adults with increased risk for the occurrence of functional impairment, cognitive deterioration, hospitalization, and all‐cause mortality . With these clinical perspectives, SPPB has been served as the main criterion for selecting study populations or a key outcome measure for efficacy in clinical research focusing on the physical performance of the older adults …”
mentioning
confidence: 99%
“…Since its development, numerous studies have shown discrimination ability of the SPPB in evaluating the functional status of older adults. For instance, studies have shown that worse physical performance based on the SPPB is associated in older adults with increased risk for the occurrence of functional impairment, cognitive deterioration, hospitalization, and all‐cause mortality . With these clinical perspectives, SPPB has been served as the main criterion for selecting study populations or a key outcome measure for efficacy in clinical research focusing on the physical performance of the older adults …”
mentioning
confidence: 99%
“…In addition, we found that the SPPB summary score, a cutoff score of <10, provided the most accurate determination of the prolonged postoperative LOS. Moreover, this cutoff value may also be used to identify older persons with chronic obstructive pulmonary disease at high risk of functional impairment 24 and mobility limitations 25 . Also, SPPB scores <7 are generally associated with a higher fall rate in the elderly; an SPPB score <5 could identify patients at major risk of death after discharge from acute care hospitals.…”
Section: Sppb Scores Predictive Of Hospital Length Of Staymentioning
confidence: 99%
“…The SPPB represents the sum of the results from three component tests of functional relevance: standing balance, 4MGS, and 5STS. 12 Research has shown that poor performance on SPPB is highly predictive of subsequent disability and mortality. 13 18 .…”
Section: Introductionmentioning
confidence: 99%
“…[28]. Patients completed the short physical performance battery (SPPB) with a score <10 points considered the threshold for mobility limitation [29].…”
Section: Sample Descriptive Measuresmentioning
confidence: 99%